Effect of Raw Food Consumption on Incidence of Hepatitis A - Insyirah N. Fadhilah; Bradley J. Waleleng; Bisuk P. S. Nainggolan (Universitas Sam Ratulangi, 2022)
Abstract: Hepatitis A is an acute infection of the liver caused by hepatitis A virus (VHA). The hepatitis A virus can be transmitted by fecal-oral route from person to person or through consumption of contaminated raw food. This study aimed to determine the effect of raw food consumption on the incidence of hepatitis A. This was a literature review study using three databases, namely Pubmed, ClinicalKey and Google Scholar. The results obtained 10 articles about several types of raw food previously contaminated that could cause hepatitis A inter alia shrimp, fish, meat, vegetables, frozen berries, dates, strawberries, and fresh vegetables. The route of contamination in raw food was most likely in the place of production before harvest as well as during harvest, packaging process, and food processing before serving. It was found that the number of cases exposed to raw food consumption was more than half of the population in almost all literature. Based on the type of raw food, the highest percentage of cases was 96.77% for dates and the lowest percentage of cases was 4.1% for meat. In conclusion, there is an effect of raw food consumption on the incidence of hepatitis AKeywords: raw food; viral contamination; hepatitis AÂ Abstrak: Hepatitis A adalah infeksi akut pada hati yang disebabkan oleh virus hepatitis A (VHA).Â Virus hepatitis A dapat ditularkan melaui rute fecal-oral dari individu ke individu atau melalui konsumsi makanan mentah yang terkontaminasi. Penelitian ini bertujuan untuk mengetahui adanya pengaruh konsumsi makanan mentah terhadap kejadian hepatitis A. Jenis penelitian ialah literature review dengan pencarian data menggunakan tiga database yaitu Pubmed, ClinicalKey dan Google Scholar. Hasil penelitian mendapatkan 10 artikel untuk dikaji mengenai jenis makanan mentah yang sebelumnya sudah terkontaminasi dan menyebabkan hepatitis A. Jenis makanan mentah yang ditemukan yaitu udang, ikan, daging, sayuran, buah beri beku, kurma, stroberi dan lalapan. Rute kontaminasi pada makanan mentah kemungkinan besar berasal dari tempat produksi baik sebelum panen maupun saat panen, proses pengepakan, dan pada proses pengolahan makanan sebelum disajikan. Jumlah kasus terpapar karena konsumsi makanan mentah lebih dari setengah jumlah populasi pada hampir semua literatur. Berdasarkan jenis makanan mentah, persentase kasus tertinggi ialah 96,77 % untuk kurma dan persentase kasus terendah ialah 4,1 % untuk daging. Simpulan penelitian ini ialah terdapat pengaruh konsumsi makanan mentah terhadap kejadian hepatitis A.Kata kunci: makanan mentah; kontaminasi virus; hepatitis A